1974
DOI: 10.1007/bf00390497
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of calcium and kinetin on ethylene production by the mungbean hypocotyl

Abstract: A slight increase in ethylene production resulted from the application of either kinetin or Ca(2+) to mungbean (Phaseolus mungo L.) hypocotyl segments, but a remarkable synergistic increase in C2H4 production was observed when they were applied together. The induction time was about 6 h as compared to 1 h for auxin-induced C2H4 production. A slight stimulation of C2H4 production was also observed when Ca(2+) was applied with abscisic acid, but no synergistic effect of Ca(2+) was observed with indole-3-acetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Bars indicate SE. studies found a 6 h lag period in kinetin-induced ethylene production in etiolated mung bean hypocotyl segments (7). Previous studies in this laboratory have found a readily measurable increase in ethylene production from etiolated mung bean hypocotyl segments within 2 h of TDZ treatment (13).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Bars indicate SE. studies found a 6 h lag period in kinetin-induced ethylene production in etiolated mung bean hypocotyl segments (7). Previous studies in this laboratory have found a readily measurable increase in ethylene production from etiolated mung bean hypocotyl segments within 2 h of TDZ treatment (13).…”
Section: Discussionmentioning
confidence: 64%
“…In cotton, TDZ was far more effective than the auxin 2,4-D in stimulating ethylene production while in sunflower the reverse was true. Cytokinins have been shown to enhance ethylene production in root (12), epicotyl (3), hypocotyl (7,13) and leaf tissues (2,9,14). In these cases the cytokinins studied were much less effective than auxins and the maximum stimulation observed was generally small (less than 10 x control).…”
Section: Discussionmentioning
confidence: 98%
“…We have demonstrated a synergistic stimulation of ethylene production by kinetin and Ca2` (12). Three mechanisms are possible to account for the interaction between kinetin and Ca2" ions: (a) Ca2+ affects the uptake and metabolism of kinetin, which is in turn responsible for ethylene production; (b) kinetin affects the uptake or transport of Ca2, ( 55,1975 Plant Physiol.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously reported a large synergistic increase in ethylene production by mung bean (Phaseoluts aureus Roxb) hypocotyl segments when kinetin and Ca2+ were applied (12). The amount of ethylene produced was dependent on the concentrations of kinetin and Ca2+ ion applied.…”
mentioning
confidence: 96%
“…Cytokinins are more effective in stimulating ethylene production in conjunction with auxin, particularly in young tissue (Fuchs and Lieberman, 1968;Aharoni et al, 1979). Lau and Yang (1974) reporteti that the stimulation of ethylene production by cytokinin in conjunction with auxin was different from the stimiilation by cytokinin plus Ca2+. In particular, the time couise for the production of ethylene differed under the two cmditions.…”
Section: Coupling Cytokinin Action To Ethylenementioning
confidence: 99%